PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA DUMAI - Octoriana, Sheila; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Regional Water Company (PDAM) is one of the agencies that often gets complaints from the public as customers about the quality of its services. The complaint is about the services of officers who are slow and not maximal. The research method used in this study is a quantitative research method with a quantitative descriptive approach. The study sample was taken as many as 100 respondents and the technique used was cluster random sampling. The data in this study used randomized questionnaires to the Customers of the Regional Water Company (PDAM) in Dumai City. The results of this study indicate that the variable quality of service on the reliability indicator gets the highest score of 985 and the lowest score is the Assurance indicator with a score of 731. As for the customer satisfaction variable the indicator of recommended availability gets the highest score with 752 and the score the lowest is obtained by the indicator of expectations of suitability with a score of 574. research conducted on the variable Quality of service to customer satisfaction shows that the service quality count value is 5.544 with a significance value of 0,000 smaller than 0.05 and regression coefficient of 13,382. This means that proven service quality and customer satisfaction have a significant effect. Keywords: Service Quality, Customer Satisfaction